2016
DOI: 10.1021/acs.langmuir.5b04287
|View full text |Cite
|
Sign up to set email alerts
|

Wetting of Hydrophilic Electrospun Mats Produced by Blending SEBS with PEO–PPO–PEO Copolymers of Different Molecular Weight

Abstract: The interaction of electrospun mats with water is critical for many possible applications, and the water contact angle on the surface is the parameter usually measured to characterize wetting. Although useful for hydrophobic surfaces, this approach is limited for hydrophilic mats, where wicking has also to be considered. In this case, it is still unclear how the fiber surface chemical composition and morphology will affect the wetting behavior of electrospun mats. In this work, wetting was studied with differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…These new equilibrium morphologies help to explain the remarkable segregation and the evolution towards surface enrichment and saturation in the SEBS/PEO-PPO-PEO blends. As previously proposed, the low surface energy PPO block drives the segregation of the amphiphilic PEO-PPO-PEO to the surface [13,18]. Pure PEO and F127 have a similar molecular weight but the segregation is much more effective with the amphiphilic polymer.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…These new equilibrium morphologies help to explain the remarkable segregation and the evolution towards surface enrichment and saturation in the SEBS/PEO-PPO-PEO blends. As previously proposed, the low surface energy PPO block drives the segregation of the amphiphilic PEO-PPO-PEO to the surface [13,18]. Pure PEO and F127 have a similar molecular weight but the segregation is much more effective with the amphiphilic polymer.…”
Section: Resultsmentioning
confidence: 59%
“…Similarly, the F127_15 mat that was hydrophobic right after processing also became hydrophilic, although the droplet absorption time varied greatly depending on the mat region [13]. These results led to the investigation presented in Figure 3a 1 Values taken from ref [30] The harmonic mean equation was used to calculate the interfacial tension γ 12 between the polymers 1 (SEBS or PS) and 2…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 64 ] Kurusu designed wetting hydrophilic electrospun mats of different molecular weights and found that the fiber diameter increased with increasing molecular weight at various concentrations of the polymer solution. [ 65 ] However, for some materials (such as dextran), the molecular weight has no significant effect on the nanofiber diameter. [ 62 ]…”
Section: Effective Parameters For Electrospinningmentioning
confidence: 99%
“…Electrospinning is a simple and low cost way to fabricate ultrathin nanofibers, which has been a promising technique in various fields including air filtration, water purification, tissue scaffolds, catalysis, flexible electronic, microwave absorption, high sensitivity sensing, and energy storage . Nevertheless, the low productivity and nonuniform collection of nanofibers are the main limitations for its industrial applications.…”
Section: Introductionmentioning
confidence: 99%